(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The given article deals with the ways of abbreviation word building in electronic correspondence on the material of the English language. E-correspondence refers to the means of communication realized by the exchange of electronic written messages. Written messages can be of different types, ranging from conventional standard emails and ending with the posts on the personal pages of social network Facebook or captions to photos in Instagram. Each of the types of electronic exchange of written communications has its own unique characteristics, but there is a linguistic feature which brings together all kinds. Consistent use of abbreviations such as acronyms can be observed